Powerful quasars with young jets in multi‐epoch radio surveys. Issue 9 (25th November 2021) - Nyland, Kristina; Dong, Dillon Z.; Patil, Pallavi; Lacy, Mark; van Velzen, Sjoert; Kimball, Amy E.; Sarbadhicary, Sumit K.; Hallinan, Gregg; Baldassare, Vivienne; Clarke, Tracy E.; Goulding, Andy D.; Greene, Jenny; et al.
Abstract: Energetic feedback driven by the large‐scale (100's of kpc) lobes of classical radio galaxies is known to play an important role in shaping galaxy evolution. However, the prevalence of young and compact jets – and their impact on the interstellar medium – remains an open question. Multi‐epoch radio surveys with cadences of years to decades offer a promising means of identifying even faint (mJy‐level) jets that are compact and potentially young on the basis of variability. Recently, a comparison of images from the Very Large Array Sky Survey (VLASS) and the Faint Images of the Radio Sky at Twenty Centimeters (FIRST) survey has revealed a population of distant ( 0.2 < z < 3.2 ) quasars that have brightened dramatically in the past 1–2 decades. These quasars appear to have transitioned from "radio‐quiet" nondetections in FIRST to "radio‐loud" detections in VLASS. Extensive multiband follow‐up observations with the VLA from 1 to 18 GHz have revealed compact (sub‐kpc) radio sources that are consistent with young jets that were recently triggered. Here, we summarize the status of our on‐going study of quasars with newborn jets identified in the radio time domain.